(untitled) - Silfvast, William (Cambridge, UK, 2004)
An introductory text to the physical and engineering principles of laser operation and design written for senior undergraduates or first year graduate students. Silvfast (physics and electrical engineering, U. of Central Florida) road tested the presentation in his own classes and devotes ample space to examples, and homework problems to bolster the subjects of fundamental wave properties and quantum properties of light, laser amplifiers, laser resonators, laser systems, and frequency multiplication of laser beams. Includes illustrations.
Keywords: Lasers